Induction Motor Energy Efficiency Investigation - István Szénásy; Dániel Csikor (Engineering Proceedings)
The energy efficiency of the induction motor (IM) is extremely important in the drives of electric vehicles. The first part of the article examines the possibilities of modifying the torque and efficiency curves in order to realize high-torque work points more efficiently by modifying the motor’s impedances. Later, it analyzes the flux-dependent changes in the highly load-dependent efficiency based on the literature. The FEM-type investigations of the experimental IM development carried out at the Vehicle Industry Research Center Institute of the Széchenyi István University offer new control options for increasing the efficiency of work points with lower torque and speed as well as for modifying the examined torque curve sections.